Factors influencing reproductive health behaviour of female non-academic staff in the Nigerian Universities (2016)
It has become imperative that there is the need to tackle reproductive health problems in Nigeria because many women die due to pregnancy related complications. However previous studies on women's reproductive health behaviour had focused majorly on adolescents, rural and non-literate women without due consideration for females in the forma! wage system. Thus leading to a dearth of literature on reproductive health behaviour of the working class women particularly those in Universities. This study examined the influence of some factors on reproductive health behaviour among female non- academic staff in the Nigerian universities. The study adopted descriptive research design of an ex-postfacto type I he simple random sampIing technique was used to select 217 female non-academic staff from purposively selected five Nigeria universities.. The instruments used were Reproductive Health Behaviour Scale (r=f).8l).Age at marriage and Reproductive Health Behaviour Scale (r-0.79). Socio-economic status and Reproductive Health Behaviour Scaleir- 0 79.). Educational attainment and Reproductive Health Behaviour Scale(r=0.75). These were complemented with three sessions of Focus Group Discussions (FGDs) and two sessions of In-depth interview (11)1) with female non-academic staff from each of the five Nigerian universities. Three hypotheses were tested at 0.05 level of significance. Data were subjected to Pearson's Product Moment correlation and content analysis. The findings indicated that there was significant relationship between reproductive health behaviour and age at marriage of female non-academic staff in the Nigerian Universities, (r - .568' \ p<.05). There was significant relationship between reproductive health behaviour and socio-economic status of female non-academic staff in the Nigerian Universities (r = - 449'. p<.05). There was significant relationship between reproductive health behaviour and educational attainment of female non-academic staff in the Nigerian Universities/r = .511'. p< 05).Age at marriage, socio-economic status and educational attainment strongly influenced reproductive health behaviour of female non-academic staff in the Nigerian Universities. However, to ensure improved reproductive health behaviour of female non-academic staff, there is the need to strengthen the use of mass media complimented with women's networking groups and religious institutions aimed at promoting better reproductive health behaviour